Political Science in the Legacy of Classical Islamic Literature - Taha J. al 'Alwani (International Institute of Islamic Thought, 1990)
In my own limited knowledge I know of no specialized studies in our classical legacy which could be described today as political thought, or as treatises on political systems, international relations, systems of government, the history of diplomacy, political development, methods of political analysis, political theory, political planning, or any of the other categories currently studied as a part of contemporary knowledge. Nonetheless, many of the issues discussed on these subjects were treated in the classical legacy through the medium of fiqh (laws of Islam), which in its long history touched upon many of the subjects studied today in the social sciences. Likewise, many of the questions dealt with in the field of political science were addressed by the early scholars of Islam within the framework of their writings on classical Fiqh of al Ahkam al Sultaniyah (the Precepts of Power). Perhaps the book written by Shaykh Ibn Taym-yah, al Siyasah al Shar’iyah, was one of the most distinctive efforts in this direction as well as the book by al Khatib al Iskafi, Lutf al Tadbir, which also dealt with certain issues which remain relevant today. Similar to such works are Suluk al Malik Fi Tadbir al Mamalik, Bada’i al-Silk, and others. These works show that the meaning of politics to the Muslim mind, and as envisioned by Islam, involves making arrangements for mankind in accordance with the values prescribed by Allah (SWT) for the realization of His purposes in creation, and in fulfillment of the trust of vicegerency, the duties of civilization, and the responsibility of the Ummah to act as a witness unto all mankind in its capacity as the “Middlemost Nation.” “Making arrangements” includes reading the past and learning its lessons as well as interpreting, understanding, and analyzing the present in the light of those lessons. Other elements included in “making arrangements” are planning for the future and benefiting from all scientific knowledge that clarifies ...